Timbulan Air Limbah dan Unit Instalasi Pengolahan Air Limbah pada Fakultas Teknik Universitas Panca Bhakti Kota Pontianak - Rahsia, Shandra Andina; Widodo, Muji Listyo (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
This study aims to analyze wastewater generation and design an appropriate domestic Wastewater Treatment Plant (WWTP) for the Faculty of Engineering at Universitas Panca Bhakti Pontianak. With the campus population growth, the volume and complexity of the wastewater produced also increase. Without adequate management, this wastewater poses a potential threat to the surrounding environment. Primary data were obtained through field surveys, while secondary data were collected from water usage records and building user counts. The treatment system was designed considering key pollutant parameters to ensure compliance with applicable quality standards. Analysis indicates that a combination of biofilter and aeration systems effectively reduces primary pollutant parameters. The findings of this study are expected to support campus environmental sustainability and provide a model for WWTP implementation in other educational institutions. Further research involving domestic wastewater sampling from the faculty is recommended to optimize the WWTP design based on specific wastewater characteristics.